The Influence of App Health Detection Early Diagnosis on the Quality of Life of the Elderly at Risk of Infectious Diseases - Budi Ertanto; Endang Triyanto (Jurnal Ners, 2025)
Background: Type II diabetes mellitus in the elderly requires long-term management with optimal family support. Mobile health (mHealth) technology offers a promising intervention to improve patients’ quality of life. Objective: To evaluate the effectiveness of mHealth applications in improving quality of life among elderly patients with type II diabetes mellitus through a systematic literature review. Methods: A systematic literature review was conducted using the PRISMA approach and the PICO framework. Literature searches were performed in Google Scholar, PubMed, Alberta Health Services, and Wiley Online Library using keywords related to mHealth, quality of life, and type II diabetes mellitus. Articles were screened based on predetermined inclusion and exclusion criteria. Results: From 12 analyzed studies, mHealth application use for ≥3 months with active participation showed a significant improvement in quality of life compared to control groups. Early Detection Applications also had a positive impact on quality of life among elderly individuals at risk of type II diabetes mellitus. Conclusion: Implementation of mHealth applications focusing on lifestyle modifications effectively enhances quality of life in elderly patients with type II diabetes mellitus, supporting the use of technology-based interventions for chronic disease management..